Synthesis of Vinyl Modified Silica as a High-Performance Liquid Chromatography Stationary Phase - Alzena, Ardine Zada; Rusli, Handajaya; Alni, Anita; Amran, Muhamad Bachri (Department of Chemistry, Faculty of Sciences and Informatics, University of Jenderal Achmad Yani, 2025)
Silica can be produced through hydrolysis in alkaline conditions via the Stober process and has two main functional groups, namely siloxane (Si-O-Si) and silanol (Si-OH). Vinyl modified silica can be produced from the hydrolysis of tetraethyl orthosilicate (TEOS) and vinyl trimethoxysilane (VTMS) with 25%(v/v) ammonia. VTMS is used as a silica surface modifying agent. The resulting silica-vinyl modification is then used as a stationary phase to fill a High Performance Liquid Chromatography (HPLC) column. The aim of this research is to synthesize vinyl-modified silica as a HPLC stationary phase and test its performance. Silica-vinyl modification is carried out by first synthesizing silica from TEOS and then modifying the surface using VTMS. Characterization was carried out using a Scanning Electron Microscope (SEM) and Fourier Transform Infrared Spectroscopy (FTIR). SEM characterization gave a spherical shape and a diameter of 1.73-2.02 μm. FTIR identification gave good results with the identification of siloxane signals (Si-O-Si) at 1,097 cm-1 on silica and 2,850 cm-1 and 2,922 cm-1 which were C-H vibrations on silica-vinyl. Qualitative identification carried out by the addition of alkenes with I2 also shows the binding of vinyl groups to the silica surface. The modified silica is then loaded into a 50 mm x 4.6 mm column. The performance test was carried out by separating caffeine and paracetamol compounds. Optimum separation of MeOH:HOH 1:99 eluent with a flow rate of 1 mL/min. The resulting resolution is 1,80 and selectivity is 1.52. The resulting calibration curve has an R2 value of 0.99156 for caffeine and 0.99431 for paracetamol.